Can Lighting Influence Self-Disclosure? - Mehta, Veli; Mukherjee, Sumitava; Manjaly, Jaison A. (Frontiers in Psychology, 2017)
With the advent of social networks where people disclose a lot of their information and opinions publicly, this research attempted to re-look at the effect of environmental lighting on willingness and actual disclosure of personal information. Previous literatures mostly addressed counseling setups and the findings were mixed. In order to clarify the effect of lighting on self disclosure, two experiments were conducted with reported willingness to disclose (experiment 1) as well as actual disclosure (experiment 2) on a range of topics like social issues, body, money, work, and personality. While quite a handful of studies have reported differences in disclosure from very subtle environmental lighting manipulations, in both experiments we could not find any effect of ambient room lighting conditions on self-disclosure. These results call for caution both in over-interpreting subtle environmental effects and in increased generalization of perceptual metaphors to actual behavior.